The impact of physical education teacher support on sport participation among college students: the chain mediating effects of physical education learning motivation and self-efficacy - Su, Wenquan; Liu, Qiang (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to examine the relationship between physical education (PE) teacher support and sport participation among college students, with a particular focus on the mediating roles of PE learning motivation and self-efficacy.MethodsA cross-sectional survey was conducted using random sampling among 604 college students aged 18–29 years (354 males, 250 females; mean age = 20.44 ± 2.541 years) in Shandong Province, China. The study employed the Physical Education Teacher Support Scale, Physical Education Learning Motivation Scale, General Self-Efficacy Scale (GSES), and Sport Participation Scale. Data analyses were conducted using SPSS 27.0, PROCESS 3.5, and AMOS 24.0. Analyses included Harman’s single-factor test, reliability and validity assessments (Cronbach’s α, KMO, Bartlett’s test of sphericity, AVE, CR, CFA), descriptive statistics, Pearson correlation analysis, and mediation analysis using PROCESS Model 6.ResultsPhysical education teacher support, PE learning motivation, self-efficacy, and sport participation were all significantly positively correlated. The impact of PE teacher support on sport participation was mediated through three pathways: solely through PE learning motivation (mediating effect value: 0.146), solely through self-efficacy (mediating effect value: 0.166), and through the combined effect of PE learning motivation and self-efficacy (mediating effect value: 0.129).ConclusionPhysical education teacher support not only directly promotes college students’ sport participation but also indirectly facilitates participation by enhancing their PE learning motivation and self-efficacy.